Strategies of Young Fathers to Quit Smoking in the Context of Indonesian Men - Rohmah, Nur; Rene Lamy, Francois (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Introduction: Smoking cessation is a critical step towards improving overall health and well-being, not only for individuals but also for their families. Although young fathers who smoke may have particular difficulties while trying to stop, they can conquer their addiction with the correct techniques and assistance. Objective: This study aims to investigate the strategies used by young Indonesian fathers to give up smoking after the birth of their children. Method: We gathered thirty young fathers who were smokers at the time for semi-structured, in-depth interviews. The process of coding data from grounded theory was utilized to interpret the acquired data, even though grounded theory was not the theoretical framework used in this investigation. Results: Some informants described their efforts to change their smoking behavior, including both external and internal efforts, for both individuals who intend to quit and those who continue to smoke. Numerous additional informants mentioned external efforts. The informants have different motivations for wanting to quit smoking. According to an analysis of the interviews, there are two main sources of motivation and/or intents for quitting: internal and external cues. Conclusion: The complex experiences that young fathers have when attempting to quit smoking are influenced by some factors, including the transition to parenting, specialized support programs, and the significance of family encouragement.